Antimicrobial effects of botanicals and biocontrol agents against Phaeoisariopsis personata, the causal agent of Tikka disease of groundnut (Asian Journal of Agriculture, 2023)
Abstract. Ndifon EM. 2023. Antimicrobial effects of botanicals and biocontrol agents against Phaeoisariopsis personata, the causal agent of Tikka disease of groundnut. Asian J Agric 7: 71-75. Groundnut is highly susceptible to various pathogenic diseases, the most important of these is tikka. The aim of this study was to control the infection of groundnut caused by Phaeoisariopsis personata (Berk. & M.A.Curtis) Arx using two experiments. Each trial was set up using a completely randomized design, and each treatment was replicated thrice. Results show that Eucalyptus globulus Labill. resinous gum (at 50% and 100% concentrations) and Terminalia catappa L. resinous gum (at 50% concentration) were more effective in the inhibition of P. personata, followed by Anacardium officinale Pritz. resinous gum and T. catappa resinous gum (at 100% concentration). All the plant extracts significantly (P?0.05) inhibited the pathogen. The percentage inhibition of P. personata by plant extracts ranged between 7.9-100%. All the isolates of Trichoderma were able to inhibit P. personata effectively, but the percentage inhibition of mycelial growth of P. personata reduced gradually with time. The percentage inhibition of P. personata by Trichoderma species ranged between 24-100%. The best biocontrol treatments were T. virens isolate BGMZ2, T. harzianum isolate BGMZ4, T. hamatum isolate ZXPB, and T. harzianum isolate ZXMZ. Using these biocontrol and botanical measures to manage the tikka leaf spot of groundnut is highly recommended.
Keywords: Leaf spots, peanuts, plant extract, Trichoderma species, yield loss